The Relationship of State Power Branches in the Perspective of Trias Politika Theory After 25 Years of Reform - Haryanti, Amelia (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the configuration of relations between the branches of state power in Indonesia—executive, legislative, and judicial—from the perspective of the trias politika theory, after two and a half decades of the reform era. The 1998 reform became an important milestone in the paradigm shift in the state constitution, marked by efforts to redistribute power to erode the dominance of the executive that emerged during the New Order period. With a juridical-normative approach and qualitative-descriptive analysis methods, this study examines various laws and regulations, institutional practices, and important decisions of judicial institutions that reflect the dynamics of relations between branches of power. The findings show that although normatively there is a more proportionate separation and division of powers, there are still practical identification of the tendency to dominate the executive branch, weak legislative control, and challenges to the independence of the judiciary. The implication of this condition shows the need to substantively strengthen the principle of checks and balances, as well as continuous institutional reform so that the ideals of trias politik can be actualized in a democratic and accountable system of government.